The implications of innovations and wage structure rigidity on economic growth and unemployment: A Schumpeterian approach to endogenous growth theory - Michael Nusser (Bamberg University, Bamberg Economic Research Group on Government and Growth (BERG), 1998)
The approach put forward in this article is based on Schumpeter`s idea of creative destruction, the competitive process by which entrepreneurs are always looking for new ideas that will render their rivals` ideas obsolete. By focusing explicity on innovation as an economic activity with different economic causes and effects, this article tries to open the door to a deeper understanding of how labor market rigidities in form of wage structure rigidities affect longrun growth through their effects on economic agent`s incentives to engage in innovative or more generally knowledge-producing activities. That is, to the extent that wage structure rigidities limits the ability of a successful innovator to capture monopoly rents from his or her innovations, it will be harmful to growth and employment.
Keywords: 330; innovation; labor market rigidity; wage (structure) rigidity; economic growth; unemployment